Hulde aan Dr. Adriaan Martens, Antwerpen, Osterrieth-Huis 15 - december 1962 - van Waterschoot, J. (Gent : Erasmus, 1963)
Bibliotheek Camille Huysmans
Dedicator: Martens, Adriaan, dedicatee: Huysmans, Camille
Nederlands
Monografie